PERUBAHAN BUNYI PADA BACAAN-BACAAN GHARIB DALAM ALQURAN MENURUT TINJAUAN FONOLOGI ARAB - Iswah Adriana (OKARA: Jurnal Bahasa dan Sastra, 2017)
As the language of the Qur’an, Arabic is not only owned by speakers of the Arab nation, but also belongs to all Muslims in the world. Then it should be better for all Muslims trying to learn and study the Qur’an since the early stage of their life. Many aspects of the qur'an have been examined and learned, But it is inexhaustible and out of date, even it is getting richer and always actual. Aspect of the recitation of al-qur'an or qiraah is one of the aspects which is rarely discussed. Most of the reciters recite Qur’an as what it is contained in the written manuscripts or rasm, though there are a lot of verses (ayah) that should be read differently with the original writing, such as imalah (inclination, bending the sound of a short vowel), tashil, isymam and etc. The phenomenon of gharib reading is paid less attention by reciters. Some changes of sound in gharib reading which are viewed from Tajweed have been oftenly studied, but in this article, writer wants to study those changes of sound from Arabic phonology (al-Ashwat) perspective. From the results, it revealed that, (1) based on the form of gharib reading in the holy Qur’an according to Imam Ashim narrated by Hafs that have undergone changes of sound are imalah, isymam, tashil, naql, badal, mad & qasr, the change of fathah or dlammah of dlad; (2) from the process, the changes of sound in gharib reading seen from Al-aswat study resulted by the presence of interaction between adjacent sounds either the sound of consonant or vowel; such as assimilation, direct or indirect assimilation, regressive or progressive assimilation, assimilation of way pronunciation and also metathesis; and (3) Some factors underlying the occurrence of changes in sound on these gharib reading are the principle of power efficiency (The Low Of Least Effort) , the ease theory, and also the balance theory.